DESIGN OF RICE GRAIN DRYER MODEL WITH TELEGRAM NOTIFICATION - Dani Ali, Nurhalim; Marpaung, Noveri Lysbetti; Suwitno,; Dian Yayan Sukma,; Anhar,; Celfin, (TESLA: Jurnal Teknik Elektro, 2024)
Rice is the staple food of the Indonesian people. Rice is produced through a lenghty process. One crucial stage of the post-harvest process is the drying of rice. The decline in rice production occurs at this drying stage. This research designs a tool that can dry rice automatically in order to facilitate the drying process of rice grain. This tool uses a DHT22 sensor as a temperature and humidity detection sensor. The Power Window motor is used as a driver of the rice rain stirring shaft that is being dried, while the Blower and Heater as a heater. This tool is equipped with NodeMCU as a microcontroller to send signals to the Telegram application on a smartphone so that status notifications on the LCD of this tool can be seen through a long distance. Testing of this tool is carried out on rice weighing 5 kg and 10 kg with a test time of 3 consecutive days. Drying is done in the morning and afternoon. Rice drying tests in the morning for 5 kg of grain are 32 minutes, 41 minutes, and 45 minutes, then 45 minutes, 55 minutes and 55 minutes for 10 kg of grain. In the afternoon, 27 minutes, 25 minutes and 29 minutes for 5 kg of grain, and 42 minutes, 38 minutes and 36 minutes for 10 kg of grain. The average grain shrinkage during the drying process in the test period was 7,5 percent for 5 kg of grain and 7,7 percent for 10 kg of grain ABSTRAK; Beras merupakan makanan pokok masyarakat Indonesia. Beras dihasilkan dengan proses yang panjang. Tahapan proses pasca panen yang sangat penting adalah pengeringan gabah padi. Penurunan produksi beras banyak terjadi pada tahapan pengeringan ini. Penelitian ini merancang alat yang dapat mengeringkan padi secara otomatis agar dapat mempermudah proses pengeringan terhadap gabah padi. Alat ini menggunakan Sensor DHT22 sebagai sensor pendeteksi suhu dan kelembaban. Motor Power Window digunakan untuk penggerak poros pengaduk gabah padi yang sedang dikeringkan, sedangkan Blower dan Heater sebagai pemanas. Alat ini dilengkapi dengan NodeMCU sebagai mikrokontroller untuk mengirim sinyal ke aplikasi Telegram pada smartphone sehingga notifikasi status pada LCD alat ini bisa dilihat melalui jarak yang jauh. Pengujian alat ini dilakukan pada padi seberat 5 kg dan 10 kg dengan lama waktu pengujian 3 hari berturut-turut. Pengeringan dilakukan pada saat pagi dan siang hari. Pengujian pengeringan padi pagi hari untuk 5 kg gabah yaitu 32 menit, 41 menit, dan 45 menit, kemudian 45 menit, 55 menit dan 55 menit untuk gabah 10 kg. Pada siang hari yaitu 27 menit,25 menit dan 29 menit untuk gabah 5 kg, dan 42 menit, 38 menit dan 36 menit untuk gabah 10 kg. Penyusutan gabah rata-rata selama proses pengeringan dalam periode pengujian alat, yaitu sebesar 7,5 persen untuk gabah seberat 5 Kg dan 7,7 persen untuk gabah seberat 10 Kg.